Metodologi Ijtihad Mazhab Indonesia: Menelusuri Pemikiran Ushul Fikih Hazairin - Moh Najib, Agus (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2016)
Hazairin is one of the pioneers who initiated the importance of  Islamic  law  with  Indonesian  pattern.  Even,  he  viewed  the importance  of  the  new  school  (mazhab)  in  Islamic  law,  namely  the Indonesian  mazhab. However, Hazairin’s thought on the methodology of ijtihad, as a basis for the establishment of a school of Islamic law, has not  been  widely  studied.  His  thought  which  was  more  studied  is  the idea  of  the  Indonesia  mazhab and  also  about  inheritance  law.  This article  specifically  explores  the  framework  of  Usul  Fiqh  proposed  by Hazairin. Epistemologically, the main topic of Usul Fiqh is about the sources of Islamic law and the method of how to formulate Islamic law from  the  source.  Therefore,  this  article  examines  Hazarin’s  thought about the two things, namely the sources of Islamic lawand its legal formulation method. From the study done, both on the  sources of law and Islamic law formulation method, Hazarin put the role of ulu al-amri (government, policy  makers)  in  a  strategic  position.  The  method  of legal formulation done by  ulu al-amrirequires  musyawarah(discussions), which  involves  jurists  and  other  relevant  scientific  experts  (collective ijtihad).  Results  of  ijtihad decided  by  ulu  al-amri will  automatically become binding formal rules of law, so that if the resultsof ijtihad is followed  and  practiced  by  the  public  widely,  it  will  become  a new school of Islamic law, namely the Indonesian mazhab.